THE INFLUENCE OF REPUTATION, DISTANCE AND INVOLUNTARY SWITCHING ON CUSTOMER SWITCHING BEHAVIOR AT PT. JNE IN MANADO - Kawengian, Kezia D.; Pangemanan, Sifrid S.; Tielung, Maria V.J (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Along with the development of technology, the internet is becoming very popular in the public, especially in the e-commerce section. Expedition business plays a key role in e-commerce because it facilitates the flow of goods to arrive at its destination. Seeing that opportunity, expedition service has become a very competitive business and it makes people confused about which expedition they want to use. Therefore, it affects the customer switching behavior, this situation is a big problem for service providers, because Customer will be reduced and profits will decrease. This study aims to determine the Influence of Reputation, Distance and Involuntary switching on Customer Switching Behavior at PT.JNE in Manado. This research applied causal type with quantitative research method. 100 respondents from customers PT.JNE in Manado were samples of this study. Findings indicate that the reputation and distance are significantly influence the customer switching behavior. Meanwhile, involuntary switching is insignificantly influenced the customer switching behavior. As a suggestion aimed at PT. JNE companies, in order to pay attention to the reputation of the company and company location or distance, because these things if not in the notice will causes the customer switching. Keywords: switching behavior, reputation, distance, involuntary switching